2019
DOI: 10.1021/acs.est.9b05486
|View full text |Cite
|
Sign up to set email alerts
|

Expression of New Pteris vittata Phosphate Transporter PvPht1;4 Reduces Arsenic Translocation from the Roots to Shoots in Tobacco Plants

Abstract: Arsenic-hyperaccumulator Pteris vittata is efficient in As uptake, probably through phosphate transporters (Pht). Here, for the first time, we cloned a new PvPht1;4 gene from P. vittata and investigated its role in arsenate (AsV) uptake and transport in yeast and transgenic tobacco plants. On the basis of quantitative real-time polymerase chain reaction (qRT-PCR), PvPht1;4 was abundantly expressed in P. vittata fronds and roots, with its transcripts in the roots being induced by both P deficiency and As exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 52 publications
4
56
0
Order By: Relevance
“…Another study also showed that heterologous expression of PvPht1;3 in tobacco increased As accumulation in the shoots by enhancing As(V) absorption and translocation (Cao et al, 2019). A recent study showed that PvPht1;4, a putative phosphate/As(V) transporter in P. vittata, had considerable As(V) and Pi transport activities when expressed heterologously in yeast (Sun et al, 2020). PvPht1;4 is abundantly expressed in P. vittata fronds and roots, with its expression in the roots being induced by both Pi deficiency and As(V) exposure (Sun et al, 2020).…”
Section: Arsenic Transporters In As Hyperaccumulator Pteris Vittatamentioning
confidence: 97%
See 1 more Smart Citation
“…Another study also showed that heterologous expression of PvPht1;3 in tobacco increased As accumulation in the shoots by enhancing As(V) absorption and translocation (Cao et al, 2019). A recent study showed that PvPht1;4, a putative phosphate/As(V) transporter in P. vittata, had considerable As(V) and Pi transport activities when expressed heterologously in yeast (Sun et al, 2020). PvPht1;4 is abundantly expressed in P. vittata fronds and roots, with its expression in the roots being induced by both Pi deficiency and As(V) exposure (Sun et al, 2020).…”
Section: Arsenic Transporters In As Hyperaccumulator Pteris Vittatamentioning
confidence: 97%
“…A recent study showed that PvPht1;4, a putative phosphate/As(V) transporter in P. vittata, had considerable As(V) and Pi transport activities when expressed heterologously in yeast (Sun et al, 2020). PvPht1;4 is abundantly expressed in P. vittata fronds and roots, with its expression in the roots being induced by both Pi deficiency and As(V) exposure (Sun et al, 2020). These results suggest that both PvPHT1;3 and PvPHT1;4 may contribute to the enhanced capacity for As(V) uptake in P. vittata, although in planta gene knockout is needed to provide direct evidence.…”
Section: Arsenic Transporters In As Hyperaccumulator Pteris Vittatamentioning
confidence: 99%
“…Therefore, we speculate that ABA may inhibit As(V) uptake through WRKY6-PHT1;1 route in Arabidopsis, which requires future investigation. It's also worthy to isolate and functionally characterize rice and brake fern homologs of AtWRKY6 in As(V) uptake because OsPT1, OsPT4, OsPT8, PvPHT1, PvPHT1;3, and PvPHT1;4 confer to As(V) accumulation and toxicity in rice and P. vittata, respectively, most likely via their role in As(V) uptake in roots (Kamiya et al, 2013;DiTusa et al, 2016;Wang et al, 2016;Cao et al, 2017;Ye et al, 2017;Cao et al, 2019;Sun et al, 2019). Arabidopsis NIP1;1, NIP3;1, NIP3;2, and NIP7;1 function in As(III) uptake and accumulation (Lindsay and Maathuis, 2017;Deng et al, 2020), however, the regulation of them being mediated by ABA is still elusive.…”
Section: Slsitmentioning
confidence: 99%
“…Thus, for designing a phytoremediation strategy, a high biomass crop can be genetically engineered by overexpression of the candidate MIP genes, particularly NIP3;1, NIP7;1, PIPs, Lsi2 and PvTIP4;1, which could increase As uptake and translocation and lead to enhanced As accumulation in genetically engineered plants. P. vittata showed increased As(V) uptake due to the increased expression of PvPHT1;3 (a phosphate transporter) and higher affinity for As(V) over phosphate [139,140]. In P. vittata, As(III) is primarily sequestered into the vacuole by PvACR3 (Arsenic Compound Resistant 3), an arsenite effluxer localized the in plasma membrane of gametophyte, and its homolog is absent in angiosperm [141].…”
Section: Genetic Engineering For Improving Arsenic Phytoremediationmentioning
confidence: 99%